Estimation of Recurrence Interval of Large Earthquakes on the Central Longmen Shan Fault Zone Based on Seismic Moment Accumulation/Release Model - Junjie Ren; Shimin Zhang (The Scientific World Journal)
Recurrence interval of large earthquake on an active fault zone is an important parameter in assessing seismic hazard. The 2008 Wenchuan earthquake (Mw 7.9) occurred on the central Longmen Shan fault zone and ruptured the Yingxiu-Beichuan fault (YBF) and the Guanxian-Jiangyou fault (GJF). However, there is a considerable discrepancy among recurrence intervals of large earthquake in preseismic and postseismic estimates based on slip rate and paleoseismologic results. Post-seismic trenches showed that the central Longmen Shan fault zone probably undertakes an event similar to the 2008 quake, suggesting a characteristic earthquake model. In this paper, we use the published seismogenic model of the 2008 earthquake based on Global Positioning System (GPS) and Interferometric Synthetic Aperture Radar (InSAR) data and construct a characteristic seismic moment accumulation/release model to estimate recurrence interval of large earthquakes on the central Longmen Shan fault zone. Our results show that the seismogenic zone accommodates a moment rate of (2.7 ± 0.3) × 1017 N m/yr, and a recurrence interval of 3900 ± 400 yrs is necessary for accumulation of strain energy equivalent to the 2008 earthquake. This study provides a preferred interval estimation of large earthquakes for seismic hazard analysis in the Longmen Shan region.